Ozaki Operation. The first experience in Ukraine - A. Gabrielyan; T. Domansky; V. Beleyovych; O. Beregovoy; S. Romanova; I. Kudlay (Ukrainian Journal of Cardiovascular Surgery, 2017)
Recently, there are increasing reports in the world on the AV valves replacement with a biological material and a new AV creation with the characteristics closest to the native one Ozaki operation (procedure) was developed by a group of authors from the University of Tojo in Tokyo (Japan), led by Shigeyuki Ozaki.The goal: is to present the results of the performed for the first time in Ukraine correction of the aortic valve by OZAKI technique.Materials and methods. The first OZAKI operation in Ukraine was executed on May 20, 2016 at the Department of Cardiac Surgery and Transplantation, at the National Institute of Surgery and Transplantation by O.Shalimov, NAMS of Ukraine. Below are shown the results of the first three transplantations completed in 2016.The postoperative period by all three patients passed without complications. Stay in ICU – 2 days. On the 7th day the patients were discharged in order to undergo the rehabilitation at the cardiology department domiciliary. After 3 and 6 months ultrasound studies data have revealed no aortic valve dysfunction. Clinically, patients feel satisfactory and have returned to the workplace. Obtained in the short and medium periods results are very encouraging.Conclusions. Our first clinical experience also showed good immediate results. The indications for the valves prosthetic surgery are not different from those with the AV replacement by bioprosthesis. The main advantage is the absence of a frame, that does not narrow the opening area of the valve and preserves the aortic root function, which is very important for patients with a narrow aortic root.